FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEBERHASILAN PROGRAM STOP BABS (BUANG AIR BESAR SEMBARANGAN) DI DESA LEDONG TIMUR KECAMATAN AEK LEDONG KABUPATEN ASAHAN TAHUN 2023 - Sinaga, Elvida Sulistiana; Siregar, Ripai; Tanjung, Rika Syahriani Br (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2023)
Currently in Indonesia there are still many health problems that have not been resolved by the Government of Indonesia. Starting from the low government budget for health to the low level of awareness of the Indonesian people about cleanliness and health, it is suspected that this is the main trigger. Based on Sanitation data from the East Ledong Community Health Center, Aek Ledong Sub District, Asahan District in 2023, there are still 38 families out of 1,524 families who have not been able to succeed in the stop babs (open defecation) program that has been implemented by the government in the last 3 years. The aim of this research was to find out the factors related to the success of the stop babs (open defecation) program. The type of quantitative research with cross-sectional design used a questionnaire instrument with interview and observation methods. The research population consisted of 38 heads of families and all of them were as samples. The research variables were analyzed univariately and bivariately with the chi square test using a p value <0.05. The results of the research on the success of the stop babs program (open defecation) were 34,2% successful and 65,8% unsuccessful. There is a relationship between knowledge (p = 0.011), attitude (p = 0.022) and the role of health workers (p = 0.036) with the success of the stop defecation program (open defecation) and there is no relationship between water availability (p = 0.190) with program success stop babs (open defecation). The community give attention to the cleanliness and maintenance of latrines that meet health requirements to prevent the spread and cases of disease.